FORMATION PROCESSES OF COMPOUND CHONDRULES IN CV3 CARBONACEOUS CHONDRITES: CONSTRAINTS FROM OXYGEN ISOTOPE RATIOS AND MAJOR ELEMENT CONCENTRATIONS - Akaki T.; Nakamura T. (My University, 2005)
We found thirty compound chondrules in two CV3 carbonaceous chondrites. The abundance in each meteorite relative to single chondrules is 29/1846 (1.6%) in Allende and 1/230 (0.4%) in Axtell. We examined petrologic features, major element concentrations and oxygen isotopic compositions. Textural, compositional and isotopic evidence suggests that multiple, different mechanisms are responsible for the formation of compound chondrules.Seven compound chondrules are composed of two conjoined porphyritic chondrules with a blurred boundary. At the boundary region of this type of compounds, a poikilitic texture is commonly observed. This suggests that the two chondrules were melted when they came to be in contact. On the other hand, seventeen compound chondrules consist of two conjoined chondrules with a discrete boundary. The preservation of spherical boundary planes of an earlier-formed chondrule of this type implies that it already solidified before fusing with a later-formed chondrule that was still melted. Six samples out of 17 compound chondrules of this type are composed of two BO chondrules. The BO-BO compound chondrules have a unique textural feature in common: the directions of the barred olivines are mostly parallel between two chondrules. This cannot be explained by a simple collision process and forces another mechanism to be taken into consideration.The remaining six compound chondrules differ from the others; they consist of an earlier-formed chondrule enclosed by a later-formed chondrule. A large FeO enrichment was observed in the later-formed chondrules and the enrichment was much greater than that in the later-formed chondrules of other types of compounds. This is consistent with the relict chondrule model, which envisages that the later-formed chondrule was made by a flash melting of a porous FeO-rich dust clump on an earlier-formed chondrule. The textural evidence of this type of compound shows that the earlier-formed chondrule has melted again to varying degrees at the second heating event. This implies that FeO concentrations in bulk chondrules increases during the second heating event if an earlier-formed chondrule was totally melted together with the FeO-rich dust aggregates.Silicate minerals such as olivine and low-Ca pyroxene in compound chondrules have oxygen isotope compositions similar to those in single chondrules from CV3 chondrites. The oxygen isotope composition of each part of the compound chondrule is basically similar to their chondrule pair, but silicates in some chondrules show varying degrees of 16O-enrichment down to −15‰ in δ18O, while those in their partners have 16O-poor invariable compositions near 0 ‰ in δ18O. This implies that the two chondrules in individual compounds formed in the same environments before they became conjoined and the heterogeneous oxygen isotope compositions in some chondrules resulted from incomplete exchange of oxygen atoms between 16O-rich chondrule melts and 16O-poor nebular gas.